Umbilical burns in neonates following traditional cord practices: A case series. Issue 1 (January 2022) - Mishra, Ankit; Atkins, Joanne; Jones, Isabel
Highlights: Traditional umbilical cord practices in Africa and Asia can involve heat treatment. Seemingly innocuous thermal exposure can result in significant injury in neonates. Immigrant mothers may bring cultural cord practices to their adopted countries. Cord burns may be misidentified as non-accidental injuries by unfamiliar clinicians. Expectant mothers in immigrant populations should be aware of these risks. Abstract: Many cultures have developed traditional practices around the management of the umbilical cord stump in the newborn. Treatment with hot water compress or fomentation is well-documented in sub-Saharan Africa but can result in thermal injuries in vulnerable neonatal skin. We report three cases of superficial partial thickness umbilical burns in infants following such treatment that presented to a paediatric burns unit in London, UK in 2020, all from a Nigerian background. In each case, the burn wound healed with conservative management only. This is a previously unreported cause of neonatal burn injury and we aim to raise awareness of the risks that traditional cord practices may pose to the newborn.